Improving Students’ Scientific Writing Skills through Discovery Learning in Science Learning: A Systematic Review - Opik Prasetyo; Bowo Sugiharto; Harlita Harlita (Jurnal Penelitian Pendidikan IPA, 2025)
Scientific writing skills are essential for students to express ideas or thoughts in various media such as practicum reports. This skills can be trained through the implementation of learning models that can empower science process skills, namely discovery learning. This study aims to analyse various articles related to the implementation of discovery learning models in science learning to improve students' scientific writing skills. This research is a systematic review with the PRISMA method using the keywords "discovery learning" and "writing skills" during the last 10 years. There are 7 articles via Scopus reviewed from 2013 – 2023. The results of the systematic review analysis showed that the implementation of the discovery learning model in science learning can improve students' scientific writing skills that consist of various aspect and criteria.  Students' learning activities in each syntax of discovery learning are suitable to empower each aspect of this skills. The systematic review of various articles on the implementation of the discovery learning model is expected to be a reference for science teachers, especially in learning biology to improve students' scientific writing skills.